2021
DOI: 10.1177/10820132211018044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lactic acid fermentation by probiotic strains on the sour cherry juice and its bioactive compounds

Abstract: Nowadays, demand for products which beyond the overall nutritional value have a feature that protects the consumers health, have increased. Several studies have proved fruit juices can become suitable carrier or medium for probiotic organisms. Therefore the aim of our study was to investigate the possibility of the probiotication of sour cherry juice by lactic acid fermentation with probiotic starter culture. In the fermentation 9 Lactobacillus strains were used and two cultivars of sour cherry as raw material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…The gallic acid, protocatechuic acid, and catechin concentrations increased with fermentation, but the total phenolic acid content decreased with the effect of storage [276]. As a result of the fermentation of cherry juice using nine Lactobacillus strains, Lactobacillus acidophilus 150 and Limosilactobacillus fermentum DT41 fermentations increased the polyphenol contents compared to the baseline [278]. Dragon fruit fermentation (Lactiplantibacillus plantarum FBS05) increased antibacterial and antioxidant activities [279].…”
Section: Fermented Fruitsmentioning
confidence: 97%
“…The gallic acid, protocatechuic acid, and catechin concentrations increased with fermentation, but the total phenolic acid content decreased with the effect of storage [276]. As a result of the fermentation of cherry juice using nine Lactobacillus strains, Lactobacillus acidophilus 150 and Limosilactobacillus fermentum DT41 fermentations increased the polyphenol contents compared to the baseline [278]. Dragon fruit fermentation (Lactiplantibacillus plantarum FBS05) increased antibacterial and antioxidant activities [279].…”
Section: Fermented Fruitsmentioning
confidence: 97%
“…The most common probiotic food products are prepared using bacteria from the Lactobacillaceae family or Bifidobacterium genus [ 38 , 39 , 40 , 41 ]. A variety of non-dairy matrices have demonstrated their potential as carriers for probiotic strains in the process of immobilization, by encapsulation or entrapment of probiotic cells on non-dairy substrates [ 42 , 43 , 44 , 45 , 46 , 47 ]. Table 1 summarises some studies for non-dairy beverages prepared from fruits and vegetables using selected characterised strains of probiotic cultures.…”
Section: Non-dairy Probiotic Beverages For Health and Nutritionmentioning
confidence: 99%
“…However, Silanikove found that approximately 75% of people worldwide have lactose intolerance and milk protein allergies, and dairy products also have a high cholesterol content, which greatly limits people's access to probiotics [13]. Therefore, it is necessary to combine the benefits of fermented plant-based substrates and probiotics [14]. As a result, new food matrices as probiotic carriers have been tested.…”
Section: Introductionmentioning
confidence: 99%